UMPSA distributes free food containers to make the Sustainability Initiative Campaign a success - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
PEKAN, 19 March 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) distributes food containers as an effort to raise awareness among its citizens about efforts to protect the environment to make the Sustainability Initiative Campaign a success in line with realizing the university's desire towards a Sustainable Campus.